2016
DOI: 10.1186/s12879-016-1715-8
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral interventions to reduce inappropriate antibiotic prescribing: a randomized pilot trial

Abstract: BackgroundClinicians frequently prescribe antibiotics inappropriately for acute respiratory infections (ARIs). Our objective was to test information technology-enabled behavioral interventions to reduce inappropriate antibiotic prescribing for ARIs in a randomized controlled pilot test trial.MethodsPrimary care clinicians were randomized in a 2 × 2 × 2 factorial experiment with 3 interventions: 1) Accountable Justifications; 2) Suggested Alternatives; and 3) Peer Comparison. Beforehand, participants completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 34 publications
1
88
0
1
Order By: Relevance
“…As this was a comparative effectiveness study without a contemporaneous control, we cannot definitively say that the interventions themselves fulfilled a causal role in reducing inappropriate antibiotic prescribing, although the natural trends in Figure suggest they did. Moreover, we did not have a safety endpoint such that we could measure an unintended harm of return visits for pneumonia or other illness progression, although recent empirical evidence suggests that this is unlikely . There is also limited generalizability since all sites were affiliated with academic health centers located in only two states.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As this was a comparative effectiveness study without a contemporaneous control, we cannot definitively say that the interventions themselves fulfilled a causal role in reducing inappropriate antibiotic prescribing, although the natural trends in Figure suggest they did. Moreover, we did not have a safety endpoint such that we could measure an unintended harm of return visits for pneumonia or other illness progression, although recent empirical evidence suggests that this is unlikely . There is also limited generalizability since all sites were affiliated with academic health centers located in only two states.…”
Section: Limitationsmentioning
confidence: 99%
“…Considerable evidence from economic theory and research in other clinical areas suggests that adding a package of feedback, nudges, and peer comparisons could dramatically improve prescribing outcomes. Our investigative team previously showed that relatively simple interventions, grounded in behavioral economics and decision science, that leverage accountability and social norms, can reduce unnecessary antibiotic prescribing for acute respiratory infection (ARI) in primary care practices . Peer comparisons dramatically improve prescribing outcomes in outpatient clinics and doctor's offices and are sustained for at least 12 months after interventions end .…”
mentioning
confidence: 99%
“…15 This strategy provides participants with information on their own performance compared to their peers to correct misperceptions about norms that may drive overuse of some tests. Previous studies found SCF to be effective in some areas of overuse (for example, in reducing inappropriate prescribing of antibiotics for acute upper respiratory infections 16,17 ). Potential advantages of SCF over other interventions include allowing ordering providers to maintain autonomy over individual decision making, which is salient in areas of practice with high clinical uncertainty, 18 and offering the potential for broad adoption of electronic medical record(EMR)-basedautomateddashboards tofacilitateautomated personalized feedback.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence both in the medical literature and in economic theory to support using a package of feedback, nudges, and peer comparisons to improve prescribing outcomes. This has been shown to reduce unnecessary antibiotic prescribing in primary care, and in one study of peer comparisons in outpatient clinics and doctor's offices, these improvements were sustained for at least 12 months after the interventions were completed …”
Section: Introductionmentioning
confidence: 96%